2019
DOI: 10.3390/jfmk4020032
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation in Primary Care. Impact of an Intervention on Perceived Self-Efficacy

Abstract: Cardiac rehabilitation is cost-effective and should be considered a part of the care system provided to patients who have suffered a myocardial infarction or another heart disease. The main variable to study was the scoring, prior to and after the intervention in the General Scale of Self-Efficacy by Baessler & Schwarzer. A clinical community trial that was open controlled and randomised was used. All adult subjects of both sexes who had completed a cardiac rehabilitation program for 12 months at the refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The total score ranges from 10 to 40, where a high total score indicates higher general self-efficacy 24. Self-efficacy has been used to evaluate interventions to strengthen the self-care capacity of patients with various chronic diseases such as diabetes25 26 and patients with CHD 27–29. It has been translated and psychometrically evaluated among a general Swedish population 30.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score ranges from 10 to 40, where a high total score indicates higher general self-efficacy 24. Self-efficacy has been used to evaluate interventions to strengthen the self-care capacity of patients with various chronic diseases such as diabetes25 26 and patients with CHD 27–29. It has been translated and psychometrically evaluated among a general Swedish population 30.…”
Section: Methodsmentioning
confidence: 99%
“…24 Self-efficacy has been used to evaluate interventions to strengthen the selfcare capacity of patients with various chronic diseases such as diabetes 25 26 and patients with CHD. [27][28][29] It has been translated and psychometrically evaluated among a general Swedish population. 30 In this study, internal consistency reliability indicated acceptable values with Cronbach's alpha 0.914.…”
Section: Self-reported Measuresmentioning
confidence: 99%